From: Keesings Wereldgebeuren in Beeld, 1936, p.720. On Masaryk's 86th birthday. From left to right: Soukop, Malypetr, Masaryk, Hodza
From: Keesings Wereldgebeuren in Beeld, 1936, p.720. On Masaryk's 86th birthday. From left to right: Soukop, Malypetr, Masaryk, Hodza.